Conceptual model of sustainable development of pedagogical staff competences in quality assurance of higher education - Biloshchytskyi, Andrii; Kuchanskyi, Oleksandr; Andrashko, Yurii; Mukhatayev, Aidos; Kassenov, Khanat (Frontiers in Education, 2025)
Creating strategies to improve the quality of higher education is the key task of higher education institutions in the conditions of rapid changes in the content of competencies, in particular IT-competencies, as well as in the conditions of turbulence in the external environment, in particular epidemics, military conflicts, etc. The article describes the conceptual model of sustainable development of teachers’ competences in ensuring the quality of higher education in higher education institutions. The sustainability of the development of teachers’ methodological competences is ensured by monitoring their activities based on the results of professional development and acquisition of the appropriate level of competence, as well as on the results of teaching by these teachers of relevant educational components in academic groups of higher education students. In order to reduce the risks of failing to pass the course, some participants of the competence project proposed to form a pool of potential project participants. Methods of optimization theory were used to solve the problem of selecting participants in the competence project. Also, the methodology of project management and pedagogical modeling was used to form the structure of the competence project and to plan its implementation. The assessment of methodological competences of university lecturers is crucial for building sustainable inter-university scientific and educational communities. Based on the results of the pilot implementation of the first stage of the competence project, project participants were selected on the basis of this conceptual model and training was organized to improve the level of competence in the field of education quality management. The results of training of teachers according to the described conceptual model allow to increase the level of their methodological competence. The obtained result requires clarification after completing the second stage of the competency-based project. Thus, the authors proposed an innovative approach to improving the level of competence of teachers of higher education institutions, which is focused on the effective assimilation of learning outcomes not only directly by teachers, but also by students of academic groups in which these teachers teach.